Prospects for Developing PR Communications in the Art Business (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Digital technologies and social media have revolutionized public relations (PR) in the art business, enabling artists, galleries, and museums to reach global audiences, attract new followers, and foster interactive relationships. This paper employs a qualitative analytical approach—reviewing existing literature, industry reports, and case examples—to identify the advantages of digital PR, outline key tools and strategies (websites, social networks, email marketing, blogs, virtual/augmented reality), discuss ethical considerations, and highlight challenges and solutions. Findings indicate that targeted, interactive, and data-driven digital PR significantly enhances engagement, cost-effectiveness, and innovation in art promotion. Future directions include leveraging artificial intelligence, blockchain, and personalized experiences to sustain competitiveness in an ever-evolving digital landscape.